Pengaruh Kepemimpinan dan Efikasi Diri Terhadap Kinerja Karyawan Melalui Komitmen Organisasi Sebagai Variabel Intervening Pada Cafe Kopi Nako Kuntum - Sudarijati Sudarijati; Erni Yuningsih; Kiki Zakiyah (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
AbstractPerformance is an important thing to achieve the goals of a company. Leadership, self-efficacy and organizational commitment is one of the things that influence employee performance, so it is appropriate for companies to pay attention to these things to develop and run the company in order to achieve goals. This study aims to determine the effect of leadership and self-efficacy on organizational commitment, to determine the effect of leadership, self-efficacy and organizational commitment on employee performance and to analyze organizational commitment capable of mediating the influence of leadership and self-efficacy on employee performance. The research method used is path analysis. The sample used in this study were all employees of Café Kopi Nako Kuntum, totaling 36 people. The results of the study show that simultaneously and partially the variables of leadership and self-efficacy have an effect on organizational commitment, then leadership, self-efficacy and organizational commitment simultaneously and partially have a positive and significant effect on employee performance, and there is an influence of leadership, self-efficacy on employee performance through organizational commitment at Café Kopi Nako Kuntum. Keywords: Employee performance; leadership; organizational commitment; self-efficacy